A lightweight high-strength three-dimensional continuous fiber reinforced cement-based panel material and a preparation method thereof
Patent Information
- Application Number
- CN202611205363.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]本发明的目的是为了解决当前适配连续纤维网格的水泥基板材密度偏高、成本偏高的问题,提供一种轻质高强连续纤维增强水泥基板材及其制备方法,在保证水泥基材料中骨料能够顺利穿透10mm×10mm三维连续纤维小网孔的前提下,通过采用空心玻璃微珠和2~5mm轻质陶粒替代常规粗骨料降低材料密度,并利用三维立体连续纤维网格的协同增强效应补偿因轻质化导致的强度损失,预期实现板材表观密度1500~1800kg/m3且抗折强度满足使用要求的技术目标
1、小网孔立体纤维网格适配:通过采用空心玻璃微珠(粒径10~200μm)和2~5mm高强轻质陶粒替代常规粗骨料,全部轻质骨料能够顺利穿透10mm×10mm的三维立体纤维网小网孔,预期与三维连续纤维网中的空间纤维束形成有效的骨料咬合,避免常规粗骨料无法穿透网孔导致的蜂窝麻面缺陷。
Smart Images

Figure CN122958128A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of continuous fiber concrete technology, specifically to a lightweight, high-strength three-dimensional continuous fiber reinforced cementitious board and its preparation method. Background Technology
[0002] In the field of continuous fiber reinforced concrete panels, existing technologies mainly employ ultra-high performance concrete (UHPC) or high-strength concrete combined with three-dimensional fiber meshes. While UHPC ensures aggregate penetration through the fiber mesh and provides excellent flexural strength, its apparent density typically exceeds 2000 kg / m³. 3 The material cost is as high as 2500~3500 yuan / m² 3 (Including steel fibers), it suffers from high density and excessive cost. The standard for Grade I slabs in "3D Fiber Reinforced Concrete (3DFRC) Slabs" (T / CBMF347-2025) requires a bulk density ≥2.1 g / cm³. 3 The density is relatively high, and density is not a crucial control parameter for decorative substrates. While meeting the flexural strength requirements of the substrate, appropriately reducing the density facilitates transportation and installation. Conventional lightweight concrete, although having a lower density, suffers from aggregate buildup and honeycomb defects at the mesh due to the large particle size of the coarse aggregate, preventing effective integration with the three-dimensional fiber mesh. Therefore, there is an urgent need for a cement-based material that can penetrate a 10mm×10mm small-mesh fiber mesh while possessing both low density and high flexural strength.
[0003] Therefore, it is necessary to propose a lightweight, high-strength three-dimensional continuous fiber-reinforced cement-based board and its preparation method to address the above-mentioned technical problems. Summary of the Invention
[0004] The purpose of this invention is to address the problems of high density and high cost in current cement-based panels adapted to continuous fiber meshes. It provides a lightweight, high-strength continuous fiber reinforced cement-based panel and its preparation method. While ensuring that the aggregate in the cement-based material can smoothly penetrate the 10mm×10mm three-dimensional continuous fiber mesh, the material density is reduced by replacing conventional coarse aggregates with hollow glass microspheres and 2-5mm lightweight ceramsite. Furthermore, the synergistic reinforcement effect of the three-dimensional continuous fiber mesh compensates for the strength loss caused by lightweighting. The expected apparent density of the panel is 1500-1800 kg / m³. 3 Furthermore, its flexural strength meets the technical objectives required for use.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: A lightweight, high-strength three-dimensional continuous fiber reinforced cement-based board comprises a cement-based material and a three-dimensional continuous fiber mesh. The mesh has a mesh size of 10mm × 10mm and a mesh height of 10~20mm. The cement-based board has a thickness of 10~20mm and an apparent density of 1500~1800kg / m³. 3 .
[0006] Preferably, the fibers of the three-dimensional continuous fiber mesh are one of basalt fiber and glass fiber, or a mixture of basalt fiber and glass fiber.
[0007] Preferably, the cement-based material comprises the following components by weight: 100 parts cement; 40-75 parts of slag powder; 15-25 parts silica fume; 20-65 parts of hollow glass microspheres; 60-105 parts of high-strength lightweight ceramsite; 80-130 parts fine sand; 3-5 parts water-reducing agent; 40-65 parts water; 0.3 to 1 part of chopped fibers; The hollow glass microspheres have a particle size of 10~75μm, the high-strength lightweight ceramic particles have a particle size of 2~5mm, and all aggregates can pass through the small mesh of a 10mm×10mm three-dimensional continuous fiber network.
[0008] Preferably, the cement-based material comprises, by weight, 50 parts of slag powder, 20 parts of silica fume, 30 parts of hollow glass microspheres, 100 parts of high-strength lightweight ceramsite, 125 parts of fine sand, 3.5 parts of water-reducing agent, 47.5 parts of water, and 0.5 parts of chopped fiber.
[0009] Preferably, the water-cement ratio of the cement-based material is 0.28 to 0.35, and the mineral admixture replacement rate is 35% to 50%.
[0010] Preferably, the hollow glass microspheres have a sphericity of not less than 95%, a particle size of 15~75μm, and a bulk density of 300~340g / cm³. 3 Compressive strength ≥80MPa, true density 0.58~0.62g / cm³ 3 The bulk density of the high-strength lightweight ceramsite is no greater than 600 kg / m³. 3 The cylinder compressive strength is ≥4MPa.
[0011] Preferably, the cement is P·O42.5 grade or P·II52.5 grade silicate cement; the slag powder is S95 grade or S105 grade slag powder; the silica fume has an SiO2 content of not less than 90%; the fine sand is shale sand or quartz sand with a particle size range of 0.075~2mm; and the water-reducing agent is a polycarboxylate high-performance water-reducing agent with a water reduction rate of not less than 30%.
[0012] Preferably, the chopped fiber is one or more of chopped basalt fiber, chopped PVA fiber, or chopped polypropylene fiber, and the fiber length is 6-12 mm.
[0013] A method for preparing a lightweight, high-strength, three-dimensional continuous fiber-reinforced cementitious board includes the following steps: S1. Weigh out the following raw materials according to the stated mass proportions: cement, slag powder, silica fume, hollow glass microspheres, high-strength lightweight ceramsite, fine sand, water-reducing agent, water, and chopped fibers; pre-wet the high-strength lightweight ceramsite to achieve a surface moisture content of 5% to 10%. S2. Add cement, slag powder, silica fume and fine sand into the mixer and dry mix for 1-2 minutes until uniform; S3. Add hollow glass microspheres and pre-wetted lightweight ceramsite to the mixer and continue mixing for 1-2 minutes until the lightweight aggregate is evenly dispersed. S4. Sprinkle the chopped fibers evenly into the mixture and continue stirring for 1-2 minutes until the fibers are evenly dispersed and free of clumps; S5. Add the pre-mixed water and water-reducing agent to the mixer and continue mixing for 2-3 minutes until the mixture is uniform, thus obtaining the lightweight high-strength cement-based material. S6. Place the three-dimensional continuous fiber mesh in the mold, pour the above-mentioned cement-based material from directly above the mesh, vibrate to form, and cure to obtain the lightweight high-strength continuous fiber reinforced cement-based board.
[0014] The vibration molding described in step S6 uses low-frequency vibration with a frequency of 50~80Hz, an amplitude of 0.5~1.0mm, and a vibration time of 30~60 seconds to avoid the lightweight aggregate from floating and segregating. The curing described in step S6 involves first curing at room temperature for 24 hours, then demolding, and then continuing to cure for 28 days.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. Small-pore three-dimensional fiber mesh adaptation: By using hollow glass microspheres (particle size 10~200μm) and 2~5mm high-strength lightweight ceramsite to replace conventional coarse aggregate, all lightweight aggregates can smoothly penetrate the small pores of the 10mm×10mm three-dimensional fiber mesh. It is expected that they will form effective aggregate interlocking with the spatial fiber bundles in the three-dimensional continuous fiber mesh, avoiding honeycomb surface defects caused by conventional coarse aggregates being unable to penetrate the mesh.
[0016] 2. Synergistic Reinforcement of Flexural Strength by Three-Dimensional Continuous Fibers: Based on the four-point bending test of "UHPC + three-dimensional continuous fiber" flat plate, embedding a three-dimensional continuous fiber mesh into the cement-based material can increase the ultimate flexural load of the plate by approximately 57%. Based on previous experimental data, it is expected that through the synergistic reinforcement effect of the 3D fiber mesh, the flexural strength of the plate can still meet the service requirements even with a matrix density reduction of approximately 20% compared to conventional 3DFRC plates.
[0017] 3. Significantly reduced density expected: By replacing the material with two lightweight aggregates, hollow glass microspheres and lightweight ceramsite, the apparent density of the slab is expected to be reduced to 1500~1800 kg / m³. 3 Compared to conventional 3DFRC sheets (density ≥ 2100 kg / m³), 3 The density is reduced by approximately 20% to 30% compared to conventional UHPC-compatible fiber mesh boards (density ≥ 2400 kg / m³). 3 It decreases by approximately 25% to 37%.
[0018] 4. Significantly reduced expected costs: Compared to existing technologies using UHPC-adapted continuous fiber mesh (material cost 2500~3500 RMB / m) 3 This invention uses ordinary silicate cement, slag powder, silica fume, hollow glass microspheres, and lightweight ceramsite as main raw materials, with an expected material cost of ≤1200 yuan / m³. 3 This represents approximately 34% to 48% of the UHPC solution.
[0019] 5. Lightweight aggregate segregation control: By pre-wetting the lightweight ceramsite and using a low-frequency vibration molding process, the problem of floating and segregation of lightweight aggregate during mixing and molding is suppressed, ensuring the uniformity of aggregate distribution inside the slab. Attached Figure Description
[0020] The specific embodiments of the invention will be described in further detail below with reference to the accompanying drawings.
[0021] Figure 1 This is the process for preparing the lightweight, high-strength substrate of the present invention; Figure 2 This is a schematic diagram of the three-dimensional continuous fiber structure of the present invention; Figure 3 This is a schematic diagram of the lightweight, high-strength continuous fiber-reinforced cement substrate structure of the present invention. Figure 4 This is a partially enlarged schematic diagram of the cement substrate A of the present invention; Detailed Implementation
[0022] To enable those skilled in the art to better understand the present invention, the technical solution of the present invention will be further described in detail below with reference to specific embodiments.
[0023] like Figures 1 to 4 As shown, a lightweight, high-strength three-dimensional continuous fiber reinforced cement-based board comprises a cement-based material and a three-dimensional continuous fiber mesh. The mesh size is 10mm × 10mm, and the mesh height is 10~20mm. The cement-based board has a thickness of 10~20mm and an apparent density of 1500~1800kg / m³. 3 .
[0024] Furthermore, the fibers of the three-dimensional continuous fiber mesh are either basalt fiber or glass fiber, or a mixture of basalt fiber and glass fiber.
[0025] Furthermore, the cement-based material comprises the following components by weight: 100 parts cement; 40-75 parts of slag powder; 15-25 parts silica fume; 20-65 parts of hollow glass microspheres; 60-105 parts of high-strength lightweight ceramsite; 80-130 parts fine sand; 3-5 parts water-reducing agent; 40-65 parts water; 0.3 to 1 part of chopped fibers; The hollow glass microspheres have a particle size of 10~75μm, the high-strength lightweight ceramic particles have a particle size of 2~5mm, and all aggregates can pass through the small mesh of a 10mm×10mm three-dimensional continuous fiber network.
[0026] Furthermore, the cement-based materials, by weight, consist of 50 parts of slag powder, 20 parts of silica fume, 30 parts of hollow glass microspheres, 100 parts of high-strength lightweight ceramsite, 125 parts of fine sand, 3.5 parts of water-reducing agent, 47.5 parts of water, and 0.5 parts of chopped fibers.
[0027] Furthermore, the water-cement ratio of the cement-based material is 0.28~0.35, and the mineral admixture replacement rate is 35%~50%.
[0028] Furthermore, the hollow glass microspheres have a sphericity of not less than 95%, a particle size of 15~75μm, and a bulk density of 300~340g / cm³. 3 Compressive strength ≥80MPa, true density 0.58~0.62g / cm³ 3 The bulk density of the high-strength lightweight ceramsite is no greater than 600 kg / m³. 3 The cylinder compressive strength is ≥4MPa.
[0029] Furthermore, the cement is P·O42.5 grade or P·II52.5 grade silicate cement; the slag powder is S95 grade or S105 grade slag powder; the silica fume has an SiO2 content of not less than 90%; the fine sand is shale sand or quartz sand with a particle size range of 0.075~2mm; and the water-reducing agent is a polycarboxylate high-performance water-reducing agent with a water reduction rate of not less than 30%.
[0030] Furthermore, the chopped fibers are one or more of chopped basalt fibers, chopped PVA fibers, or chopped polypropylene fibers, and the fiber length is 6-12 mm.
[0031] A method for preparing a lightweight, high-strength, three-dimensional continuous fiber-reinforced cementitious board includes the following steps: S1. Weigh out the following raw materials according to the stated mass proportions: cement, slag powder, silica fume, hollow glass microspheres, high-strength lightweight ceramsite, fine sand, water-reducing agent, water, and chopped fibers; pre-wet the high-strength lightweight ceramsite to achieve a surface moisture content of 5% to 10%. S2. Add cement, slag powder, silica fume and fine sand into the mixer and dry mix for 1-2 minutes until uniform; S3. Add hollow glass microspheres and pre-wetted lightweight ceramsite to the mixer and continue mixing for 1-2 minutes until the lightweight aggregate is evenly dispersed. S4. Sprinkle the chopped fibers evenly into the mixture and continue stirring for 1-2 minutes until the fibers are evenly dispersed and free of clumps; S5. Add the pre-mixed water and water-reducing agent to the mixer and continue mixing for 2-3 minutes until the mixture is uniform, thus obtaining the lightweight high-strength cement-based material. S6. Place the three-dimensional continuous fiber mesh in the mold, pour the above-mentioned cement-based material from directly above the mesh, vibrate to form, and cure to obtain the lightweight high-strength continuous fiber reinforced cement-based board.
[0032] The vibration molding described in step S6 uses low-frequency vibration with a frequency of 50~80Hz, an amplitude of 0.5~1.0mm, and a vibration time of 30~60 seconds to avoid the lightweight aggregate from floating and segregating. The curing described in step S6 involves first curing at room temperature for 24 hours, then demolding, and then continuing to cure for 28 days.
[0033] Compared with the prior art, the present invention has the following beneficial effects: 1. Small-pore three-dimensional fiber mesh adaptation: By using hollow glass microspheres (particle size 10~200μm) and 2~5mm high-strength lightweight ceramsite to replace conventional coarse aggregate, all lightweight aggregates can smoothly penetrate the small pores of the 10mm×10mm three-dimensional fiber mesh. It is expected that they will form effective aggregate interlocking with the spatial fiber bundles in the three-dimensional continuous fiber mesh, avoiding honeycomb surface defects caused by conventional coarse aggregates being unable to penetrate the mesh.
[0034] 2. Synergistic Reinforcement of Flexural Strength by Three-Dimensional Continuous Fibers: Based on the four-point bending test of "UHPC + three-dimensional continuous fiber" flat plate, embedding a three-dimensional continuous fiber mesh into the cement-based material can increase the ultimate flexural load of the plate by approximately 57%. Based on previous experimental data, it is expected that through the synergistic reinforcement effect of the 3D fiber mesh, the flexural strength of the plate can still meet the service requirements even with a matrix density reduction of approximately 20% compared to conventional 3DFRC plates.
[0035] 3. Significantly reduced density expected: By replacing the material with two lightweight aggregates, hollow glass microspheres and lightweight ceramsite, the apparent density of the slab is expected to be reduced to 1500~1800 kg / m³. 3 Compared to conventional 3DFRC sheets (density ≥ 2100 kg / m³), 3 The density is reduced by approximately 20% to 30% compared to conventional UHPC-compatible fiber mesh boards (density ≥ 2400 kg / m³). 3 It decreases by approximately 25% to 37%.
[0036] 4. Significantly reduced expected costs: Compared to existing technologies using UHPC-adapted continuous fiber mesh (material cost 2500~3500 RMB / m) 3 This invention uses ordinary silicate cement, slag powder, silica fume, hollow glass microspheres, and lightweight ceramsite as main raw materials, with an expected material cost of ≤1200 yuan / m³. 3 This represents approximately 34% to 48% of the UHPC solution.
[0037] 5. Lightweight aggregate segregation control: By pre-wetting the lightweight ceramsite and using a low-frequency vibration molding process, the problem of floating and segregation of lightweight aggregate during mixing and molding is suppressed, ensuring the uniformity of aggregate distribution inside the slab.
[0038] The following examples are for illustrative purposes only and are not intended to limit the scope of protection of the present invention.
[0039] The raw materials used in each embodiment are as follows: Cement: P·O42.5 grade ordinary Portland cement; Slag powder: S95 grade slag powder; Silica fume: SiO2 content not less than 90%; Hollow glass microspheres: true sphericity not less than 95%, particle size 15~70μm, bulk density 300~340g / cm³ 3 Compressive strength ≥80MPa, true density 0.58~0.62g / cm³ 3 ; High-strength lightweight ceramsite: particle size 2~5mm, bulk density not greater than 600kg / m³ 3 The cylinder compressive strength is ≥4MPa; Shale sand: particle size range 0.075~2mm; Water-reducing agent: Polycarboxylate high-performance water-reducing agent, with a water reduction rate of not less than 30%; Short-cut fibers: Short-cut basalt fibers, 6~12mm in length; Three-dimensional continuous fiber mesh: mesh size 10mm×10mm, mesh height 10~20mm, fiber is basalt fiber.
[0040] Example 1: Example 1 is a theoretically designed mix proportion based on the principle of mix proportion design; the actual performance needs to be verified by experiments.
[0041] The following raw materials are used per cubic meter of cement-based material: 400 kg of cement, 200 kg of slag powder, 80 kg of silica fume, 120 kg of hollow glass microspheres, 400 kg of lightweight ceramsite, 500 kg of shale sand, 14 kg of water-reducing agent, 190 kg of water, and 2 kg of chopped fiber.
[0042] Converted to parts by weight (based on 100 parts of cement), the amounts of each component are as follows: 100 parts cement, 50 parts slag powder, 20 parts silica fume, 30 parts hollow glass microspheres, 100 parts lightweight ceramsite, 125 parts shale sand, 3.5 parts water-reducing agent, 47.5 parts water, and 0.5 parts chopped fiber.
[0043] The total amount of cementitious material in this mix proportion is 680 kg / m³. 3 The water-cement ratio is 0.28, and the mineral admixture substitution rate is 41.2%.
[0044] The theoretically estimated apparent density of this mix proportion is approximately 1700 kg / m³. 3 (Calculated based on the density of each component; actual density needs to be verified by actual measurement).
[0045] Example 2: Example 2 is a theoretically designed mix proportion based on the principle of mix proportion design, focusing on a high admixture substitution rate and a larger amount of hollow microspheres to pursue lower density (ultra-lightweight). Actual performance needs to be verified by experiments.
[0046] The following raw materials are used per cubic meter of cement-based material: 320 kg of cement, 230 kg of slag powder, 60 kg of silica fume, 200 kg of hollow glass microspheres, 250 kg of lightweight ceramsite, 350 kg of shale sand, 12 kg of water-reducing agent, 195 kg of water, and 2 kg of chopped fiber.
[0047] Converted to parts by weight (based on 100 parts of cement), the amounts of each component are as follows: 100 parts of cement, 72 parts of slag powder, 19 parts of silica fume, 63 parts of hollow glass microspheres, 78 parts of lightweight ceramsite, 109 parts of shale sand, 3.8 parts of water-reducing agent, 61 parts of water, and 0.6 parts of chopped fiber.
[0048] The total amount of cementitious material in this mix proportion is 610 kg / m³. 3 The water-cement ratio is 0.32, and the mineral admixture replacement rate is 47.5%.
[0049] The theoretically estimated apparent density of this mix proportion is approximately 1550 kg / m³. 3 (Calculated based on the density of each component; actual density needs to be verified by actual measurement).
[0050] Example 3: Example 3 is a theoretical mix design based on the mix design principle, which focuses on a higher cement content to ensure the strength of the matrix (high-strength type). The actual performance needs to be verified by experiments.
[0051] The following raw materials are used per cubic meter of cement-based material: 420 kg of cement, 170 kg of slag powder, 85 kg of silica fume, 100 kg of hollow glass microspheres, 300 kg of lightweight ceramsite, 450 kg of shale sand, 14 kg of water-reducing agent, 189 kg of water, and 1.5 kg of chopped fiber.
[0052] Converted to parts by weight (based on 100 parts of cement), the amounts of each component are as follows: 100 parts of cement, 40 parts of slag powder, 20 parts of silica fume, 24 parts of hollow glass microspheres, 71 parts of lightweight ceramsite, 107 parts of shale sand, 3.3 parts of water-reducing agent, 45 parts of water, and 0.4 parts of chopped fiber.
[0053] The total amount of cementitious material in this mix proportion is 675 kg / m³. 3 The water-cement ratio is 0.28, and the mineral admixture substitution rate is 37.8%.
[0054] The theoretically estimated apparent density of this mix proportion is approximately 1750 kg / m³. 3 (Calculated based on the density of each component; actual density needs to be verified by actual measurement).
[0055] Table 1 shows the theoretical raw material consumption per cubic meter of cement-based material for each embodiment. The mix proportions in the table are calculated based on the principles of concrete mix design, and the actual performance needs to be verified by experiments.
[0056] Table 1 shows the amount of raw materials used per cubic meter of concrete in each embodiment and comparative example.
[0057]
[0058] The preparation methods of the above embodiments all include the following steps: Step S1: Weigh the following raw materials according to the mass proportions described in each embodiment: cement, slag powder, silica fume, hollow glass microspheres, lightweight ceramsite, fine sand, water-reducing agent, water, and chopped fibers; pre-wet the lightweight ceramsite to achieve a surface moisture content of 5% to 10%; Step S2: Add cement, slag powder, silica fume and fine sand into a forced mixer and dry mix for 1-2 minutes until all powders and aggregates are evenly mixed; Step S3: Add hollow glass microspheres and pre-wetted lightweight ceramsite to the mixer and continue mixing for 1-2 minutes until the lightweight aggregate is evenly dispersed. Note that the hollow glass microspheres should be added slowly to avoid breakage. Step 4: Evenly sprinkle the chopped fibers into the mixture and continue stirring for 1-2 minutes until the chopped fibers are evenly dispersed in the mixture without clumping. Step S5: After pre-mixing water and water-reducing agent evenly, add them to the mixer and continue mixing for 2-3 minutes until the mixture has a uniform color and uniform fluidity, thus obtaining the lightweight high-strength cement-based material. Step S6: Place the three-dimensional continuous fiber mesh (mesh size 10mm×10mm, mesh height matching the board thickness) in the mold, and simultaneously pour the above-mentioned cement-based material from directly above the mesh. Use low-frequency vibration molding (frequency 50~80Hz, amplitude 0.5~1.0mm, vibration time 30~60 seconds), first cure at room temperature for 24 hours, then demold, and continue curing for 28 days to obtain the lightweight high-strength continuous fiber reinforced cement-based board.
[0059] Based on the concrete mix design principles and preliminary experimental data, the performance of cement-based materials in Examples 1, 2, and 3 was preliminarily analyzed. The preliminary analysis was based on the following: (1) calculation of the density contribution of each component; (2) empirical relationship between water-cement ratio and strength; and (3) reference data from the preliminary four-point bending test of high-strength cement-based materials, showing a 57% increase in flexural strength due to 3D fiber mesh. The preliminary items included: (1) Mesh penetration: Based on the matching analysis of aggregate particle size (hollow glass microspheres 15~75μm, lightweight ceramsite 2~5mm) and mesh size (10mm×10mm), it is estimated that lightweight aggregate can pass through the fiber mesh smoothly. (2) Slump: Based on the amount of cementitious material and the water-cement ratio, the estimated slump is ≥180mm; (3) 28-day compressive strength: based on a water-cement ratio of 0.28~0.32 and a total cementitious material volume of 610~680 kg / m³. 3 Empirical relationship estimation; (4) Saturated flexural strength: Based on the empirical conversion relationship between the matrix compressive strength and flexural strength (flexural strength is about 1 / 10 to 1 / 8 of compressive strength), and with reference to the 57% flexural strength improvement data of 3D fiber mesh (derived from previous high-strength matrix experiments), a comprehensive estimate was made. (5) Apparent density: a volume-weighted estimate based on the density and amount of each component; (6) Ultimate flexural load: Referring to the previous four-point bending comparison test data of high-strength cement-based materials (3D fiber mesh increased the ultimate flexural load from 8.46kN to 13.34kN, an increase of approximately 57%), the actual improvement effect under lightweight matrix conditions needs to be verified by subsequent experiments.
[0060] Table 2 Performance Design Estimates for Each Implementation Example
[0061] Based on the above performance design prediction analysis: (1) According to particle size analysis, the lightweight aggregates (hollow glass microspheres 15~75μm, lightweight ceramsite 2~5mm) of the three proportions can all pass through the 10mm×10mm fiber mesh, and it is expected that effective aggregate interlocking will be formed on both sides of the mesh to avoid quality defects such as honeycomb and pitting. (2) Based on the previous high-strength matrix experimental data (3D fiber mesh increases the bending limit load by about 57%), it is expected that after combining 3D fiber mesh with Example 1, the flexural strength of the board can meet the application requirements; the actual improvement ratio under the lightweight matrix condition needs to be verified by experiments. (3) The theoretically estimated apparent densities of the three mix proportions are all between 1500 and 1800 kg / m³. 3 Within the expected range, compared to conventional 3DFRC sheets (density ≥ 2100 kg / m³), 3 (This will decrease by approximately 20% to 30%) (4) Example 1 is expected to achieve a good balance between theoretically estimated strength, density and material cost, which is the optimal ratio for the theoretical design of this invention; (5) In Example 2, by significantly increasing the amount of hollow glass microspheres, the theoretically estimated density was further reduced to approximately 1550 kg / m³. 3 It is expected to be suitable for scenarios with extremely high requirements for lightweightness; (7) Example 3 By increasing the amount of cement and lightweight ceramsite, the matrix strength is expected to be higher, which is suitable for scenarios with high requirements for compressive strength.
[0062] Example 4: High-strength composite lightweight aggregate concrete This embodiment focuses on improving compressive strength by optimizing the activity of cementitious materials and the fiber reinforcement system. The specific solution is as follows: Raw material ratio (dosage per cubic meter): 336 kg of P·O42.5 ordinary Portland cement, 96 kg of S95 grade slag powder, 48 kg of silica fume, 320 kg of shale sand with a fineness modulus of 2.4, and 600 kg / m³ of 2-5 mm bulk density. 3260kg of high-strength lightweight ceramsite, 35kg of hollow glass microspheres with compressive strength ≥70MPa, 6kg of 12mm basalt chopped fiber + 2kg of 10mm aramid chopped fiber, three-dimensional continuous fiber web, 158kg of water, and 6.72kg of polycarboxylate high-performance water-reducing agent.
[0063] Preparation process S1 Ceramsite pre-wetting: Add water to the high-strength ceramsite and pre-wet for 12 hours, controlling the surface moisture content to 8%, and drain the surface water for later use. S2 Dry Mixing: Cement, slag powder, silica fume, and shale sand are added to the mixer and dry-mixed at low speed for 1.5 minutes until the materials are uniform; S3 Add high-strength lightweight aggregate: Pre-wetted ceramsite and hollow glass microspheres are slowly added to the mixer and stirred at low speed for 1 minute to avoid damage to the microspheres; S4 Short-Cut Fiber Dispersion: Evenly sprinkle the two types of short-cut fibers into the material and stir at medium speed for 2.5 minutes until the fibers are dispersed without clumping. S5 fiber mesh casting: Three-dimensional continuous fiber mesh is pre-laid in the mold. Dry powder is mixed with water and water-reducing agent for 2.5 minutes. Fiber mesh is laid during the casting process, and the material is slowly poured throughout. S6 low-frequency vibration molding: Vibrate at 55Hz frequency and 0.7mm amplitude for 90 seconds. After vibration to remove air, demold after standard curing for 24 hours and continue curing for 28 days.
[0064] Example 5: Ultra-lightweight thermal insulation composite lightweight aggregate concrete This embodiment focuses on reducing dry density and improving thermal insulation performance by increasing the proportion of lightweight aggregates. The specific solution is as follows: Raw material ratio (dosage per cubic meter): 266 kg of P·O42.5 ordinary Portland cement, 76 kg of S95 grade slag powder, 38 kg of silica fume, 180 kg of shale sand with a fineness modulus of 2.2, and 500 kg / m³ of 2-5 mm bulk density. 3 High-strength lightweight expanded clay aggregate, 210kg, density 0.32g / cm³ 3 The composition includes 65 kg of hollow glass microspheres, 4 kg of 8 mm PP chopped fibers + 2 kg of 10 mm basalt chopped fibers, a three-dimensional continuous fiber web, 144.4 kg of water, and 4.94 kg of polycarboxylate superplasticizer.
[0065] Preparation process S1 Ceramsite Pre-wetting: Add water to the lightweight ceramsite and pre-wet for 8 hours, controlling the surface moisture content to 6%, then drain and set aside. S2 Dry Mixing: Cement, slag powder, silica fume, and shale sand are dry mixed at low speed for 1 minute until uniform; S3 incorporates high-strength lightweight aggregates: pre-wetted ceramsite and hollow glass microspheres are added slowly in three batches, and stirred at low speed for 1.5 minutes to reduce the breakage rate of microspheres; S4 Short-Cut Fiber Dispersion: After the two types of short-cut fibers are mixed, stir at medium speed for 2 minutes to disperse evenly without clumping; S5 fiber mesh casting: three-dimensional continuous fiber mesh is pre-laid in the mold, dry powder is mixed with water and water-reducing agent for 2 minutes, fiber mesh is laid in the middle of the casting process, and the casting is slow. S6 low-frequency vibration molding: Vibration at 50Hz frequency and 0.5mm amplitude for 60 seconds to avoid the floating and segregation of light aggregates. Demolding after 24 hours of curing, and standard curing for 28 days.
[0066] Example 6: High Crack Resistance and Toughness Composite Lightweight Aggregate Concrete This embodiment focuses on improving flexural toughness and crack resistance, and optimizes the multi-fiber hybrid reinforcement system. The specific solution is as follows: Raw material ratio (dosage per cubic meter): 294 kg of P·O42.5 ordinary Portland cement, 84 kg of S95 grade slag powder, 42 kg of silica fume, 270 kg of shale sand with a fineness modulus of 2.5, and a bulk density of 550 kg / m³ (2-5 mm). 3 235 kg of high-strength lightweight ceramsite, 45 kg of hollow glass microspheres with compressive strength ≥ 55 MPa, 4 kg of 15 mm aramid chopped fiber + 3 kg of 12 mm basalt chopped fiber + 2 kg of 10 mm PP chopped fiber, three-dimensional continuous fiber web, 151.2 kg of water, and 5.88 kg of polycarboxylate superplasticizer.
[0067] Preparation process S1 Ceramsite Pre-wetting: Ceramsite is pre-wetted with water for 10 hours, controlling the surface moisture content to 9%, and then drained for later use; S2 Dry Mixing: Cement, slag powder, silica fume, and shale sand are dry mixed at low speed for 2 minutes until uniform; S3 Add high-strength lightweight aggregate: Slowly add pre-wetted ceramsite and hollow glass microspheres, and stir at low speed for 1 minute to prevent microspheres from breaking and causing dust. S4 Short-Cut Fiber Dispersion: Mix the three types of short-cut fibers and sprinkle them evenly. Stir at medium speed for 3 minutes to ensure that the fibers are completely dispersed and without clumping. S5 fiber mesh casting: pre-lay mixed three-dimensional continuous fiber mesh in layers inside the mold, mix dry powder with water and water-reducing agent for 3 minutes, lay it during the casting process, and slowly pour it in layers; S6 low-frequency vibration molding: Vibrate at 80Hz frequency and 1.0mm amplitude for 120 seconds to fully remove air bubbles, then cure for 24 hours before demolding, and standard curing for 28 days.
[0068] The control example uses a conventional high-strength lightweight aggregate concrete formula and general preparation process, without adding hollow glass microspheres or three-dimensional continuous fiber mesh, only adding PP short-cut fibers, without multi-fiber mixed reinforcement design, and serves as the benchmark group for performance comparison.
[0069] Table 3. Raw material consumption per cubic meter of concrete
[0070] Table 4 shows the performance design prediction table.
[0071] Performance design prediction analysis 1. Analysis of the difference between density and thermal insulation performance Example 5 significantly increased the proportion of hollow glass microspheres and low-density ceramsite by reducing the amount of heavy components (cement, shale sand), resulting in a dry apparent density of 920 kg / m³. 3 It is only 71.9% of the control example; the number of internal closed pores is significantly increased, the thermal conductivity is as low as 0.26W / (m・K), the thermal insulation performance is 50% higher than the control example, and it is suitable for integrated insulation of building envelope.
[0072] Example 4 has a slightly higher dry density than the control example due to the increased total amount of cementitious materials and the increased proportion of high-density, high-strength ceramsite, but it still falls within the category of lightweight concrete. Its thermal insulation performance is similar to that of the conventional group, prioritizing the structural load-bearing capacity.
[0073] The density of Example 6 was basically the same as that of the control example. The incorporation of hollow glass microspheres offset the mass increase brought about by the multi-fiber system, and there was no significant loss in thermal insulation performance.
[0074] 2. Analysis of differences in compressive strength properties Example 4: By increasing the total amount of cementitious material (480 kg / m³) 3 With a high content of active silica fume, combined with high-strength ceramsite and high-modulus basalt-aramid fiber, the 28-day compressive strength reaches 48.2 MPa, which is 50.2% higher than the control example; the layered constraint of the three-dimensional fiber network inhibits the cracking and propagation of concrete, further improving the structural strength and stability, and meeting the requirements of load-bearing structural components.
[0075] Example 5 reduces the amount of cementitious materials to achieve the goal of ultra-lightweight concrete, resulting in a slight decrease in compressive strength, but it still meets the LC20 grade lightweight aggregate concrete standard and can be used in non-load-bearing filling and thermal insulation partition wall scenarios.
[0076] Example 6 showed a 20.2% increase in compressive strength compared to the control example. The synergistic effect of the hybrid fibers and the three-dimensional mesh compensated for the insufficient interfacial strength of the lightweight aggregate, achieving a balance between strength and toughness.
[0077] 3. Analysis of the difference between toughness and crack resistance Example 6 employs a multi-level reinforcement system of "chopped hybrid fibers + three-dimensional continuous braided fiber web": chopped fibers inhibit the initiation of microcracks, while the three-dimensional continuous fiber web bears macroscopic tensile stress and prevents crack propagation. The 28-day flexural strength is increased by 102.4% compared to the control example, and the splitting tensile strength is increased by 60.7%. The drying shrinkage rate is reduced to 0.038%, which is 41.5% lower than the control example. The crack resistance toughness is significantly improved, making it suitable for components with large spans and high crack resistance requirements.
[0078] The high-modulus fiber system in Example 4 also improved the material's toughness, with flexural strength increasing by 61.9% compared to the control example and shrinkage decreasing by 20%, achieving both high strength and crack resistance.
[0079] The control example, relying solely on PP fiber, could only suppress some early plastic cracking, with limited improvement on macroscopic toughness and tensile strength, and exhibited obvious brittle characteristics.
[0080] 4. Performance gain analysis of the preparation process The pre-wetting of ceramsite, slow feeding of lightweight aggregates, and low-frequency vibration molding processes used in all embodiments effectively solve the problems of lightweight aggregates floating and segregation and glass microsphere breakage, ensuring the homogeneity of the material. Compared with conventional mixing and vibration processes, the segregation rate can be reduced by more than 30% under the same formula, further reducing the performance dispersion coefficient and improving the stability of the finished product.
[0081] The above description is merely a preferred embodiment of the present invention and does not limit the scope of patent protection of the present invention. Any equivalent structural or procedural modifications made based on the content of this specification, or direct or indirect applications in other related technical fields, are similarly included within the scope of patent protection of the present invention.
Claims
1. A lightweight, high-strength, three-dimensional continuous fiber-reinforced cementitious board, characterized in that: It comprises a mixture of cement-based materials and a three-dimensional continuous fiber mesh, wherein the mesh size is 10mm × 10mm and the mesh height is 10~20mm; the cement-based board has a thickness of 10~20mm and an apparent density of 1500~1800kg / m³. 3 .
2. The lightweight, high-strength, three-dimensional continuous fiber-reinforced cementitious board as described in claim 1, characterized in that: The fibers of the three-dimensional continuous fiber mesh are either basalt fiber or glass fiber, or a mixture of basalt fiber and glass fiber.
3. The lightweight, high-strength, three-dimensional continuous fiber-reinforced cementitious board as described in claim 1, characterized in that: The cement-based material comprises the following components by mass parts: 100 parts cement; 40-75 parts of slag powder; 15-25 parts silica fume; 20-65 parts of hollow glass microspheres; 60-105 parts of high-strength lightweight ceramsite; 80-130 parts fine sand; 3-5 parts water-reducing agent; 40-65 parts water; 0.3 to 1 part of chopped fibers; The hollow glass microspheres have a particle size of 10~75μm, the high-strength lightweight ceramic particles have a particle size of 2~5mm, and all aggregates can pass through the small mesh of a 10mm×10mm three-dimensional continuous fiber network.
4. The lightweight, high-strength, three-dimensional continuous fiber-reinforced cementitious board according to claim 3, characterized in that: The cement-based materials, by weight, consist of 50 parts of slag powder, 20 parts of silica fume, 30 parts of hollow glass microspheres, 100 parts of high-strength lightweight ceramsite, 125 parts of fine sand, 3.5 parts of water-reducing agent, 47.5 parts of water, and 0.5 parts of chopped fibers.
5. The lightweight, high-strength, three-dimensional continuous fiber-reinforced cementitious board according to claim 1, characterized in that: The water-cement ratio of the cement-based material is 0.28~0.35, and the mineral admixture replacement rate is 35%~50%.
6. The lightweight, high-strength, three-dimensional continuous fiber-reinforced cementitious board according to claim 1, characterized in that: The hollow glass microspheres have a sphericity of not less than 95%, a particle size of 15~75μm, and a bulk density of 300~340g / cm³. 3 Compressive strength ≥80MPa, true density 0.58~0.62g / cm³ 3 The bulk density of the high-strength lightweight ceramsite is no greater than 600 kg / m³. 3 The cylinder compressive strength is ≥4MPa.
7. The lightweight, high-strength, three-dimensional continuous fiber-reinforced cementitious board according to claim 1, characterized in that: The cement is P·O42.5 grade or P·II52.5 grade silicate cement; the slag powder is S95 grade or S105 grade slag powder; the silica fume has an SiO2 content of not less than 90%; the fine sand is shale sand or quartz sand with a particle size range of 0.075~2mm; the water-reducing agent is a polycarboxylate high-performance water-reducing agent with a water reduction rate of not less than 30%.
8. The lightweight, high-strength, three-dimensional continuous fiber-reinforced cementitious board according to claim 1, characterized in that: The chopped fibers are one or more of chopped basalt fibers, chopped PVA fibers, or chopped polypropylene fibers, and the fiber length is 6-12 mm.
9. A method for preparing a lightweight, high-strength three-dimensional continuous fiber-reinforced cementitious board as described in any one of claims 1-8, characterized in that, Includes the following steps: S1. Weigh out the following raw materials according to the stated mass proportions: cement, slag powder, silica fume, hollow glass microspheres, high-strength lightweight ceramsite, fine sand, water-reducing agent, water, and chopped fibers; pre-wet the high-strength lightweight ceramsite to achieve a surface moisture content of 5% to 10%. S2. Add cement, slag powder, silica fume and fine sand into the mixer and dry mix for 1-2 minutes until uniform; S3. Add hollow glass microspheres and pre-wetted lightweight ceramsite to the mixer and continue mixing for 1-2 minutes until the lightweight aggregate is evenly dispersed. S4. Sprinkle the chopped fibers evenly into the mixture and continue stirring for 1-2 minutes until the fibers are evenly dispersed and free of clumps; S5. Add the pre-mixed water and water-reducing agent to the mixer and continue mixing for 2-3 minutes until the mixture is uniform, thus obtaining the lightweight high-strength cement-based material. S6. Place the three-dimensional continuous fiber mesh in the mold, pour the above-mentioned cement-based material from directly above the mesh, vibrate to form, and cure to obtain the lightweight, high-strength continuous fiber reinforced cement-based board.
10. The method for preparing a lightweight, high-strength three-dimensional continuous fiber-reinforced cement substrate according to claim 9, characterized in that: The vibration molding described in step S6 uses low-frequency vibration with a frequency of 50~80Hz, an amplitude of 0.5~1.0mm, and a vibration time of 30~60 seconds to avoid the lightweight aggregate from floating and segregating. The curing described in step S6 involves first curing at room temperature for 24 hours, then demolding, and then continuing to cure for 28 days.